Resepsi Youtube Deddy Corbuzier dan Indonesia: Literasi Keberagaman sampai Politik Gender dan Seksualitas - Lokita Pramesti Dewi; Udi Rusadi (Da'watuna: Journal of Communication and Islamic Broadcasting, 2023)
This article tries to describe Deddy Corbuzier's YouTube podcast production, as one of the well-known YouTubers in Indonesia, who has started to warm up the broadcasting industry again on digital platforms and has succeeded in bringing the public space back to warmth with issues of gender and sexuality in most of the themes of his podcast content. In particular, the YouTube platform operates within the scope of content creators and users are provided with a unique opportunity to engage with the creation and open reception of such video content. Each other can observe the development of issues that are becoming a trend to talk about. One of them is gender and sexuality in the podcast which influences the type of discourse circulating in society. In the podcast titled #closethedoor owned by Deddy Corbuzier, every member of society can determine their mindset in conducting literacy towards gender and sexuality politics which are increasingly visible and have various appearances in Indonesia. n the other hand, some of these shows are still considered taboo as gender and sexuality politics that support sexual deviance for some Indonesian people. In analyzing this reception about Deddy Corbizer's YouTube, the researcher tries to present various kinds of productions that have emerged along with the controversy, as well as how the performance of gender and sexuality is perceived by the Indonesian people. Next, the researcher also utilized a critical discourse analysis framework from YouTube comments to produce Deddy Corbuzier's #closethedoor content, especially shows that have tendentious issues of gender and sexuality. This paper attempts to draw conclusions about the political role of gender and sexuality as well as public space which requires recognition or rejection of gender and sexuality communities.